Struktur dan Fungsi Pantun dalam Pidato Persembahan Acara Pernikahan di Kenagarian Ujung Gading Kecamatan Lembah Melintang Kabupaten Pasaman Barat - Astuti, Hendang; Zulfadhli, Zulfadhli (TSAQOFAH, 2025)
This study aims to describe the structure and function of pantun in ceremonial speeches (pidato persembahan) at wedding events in Kenagarian Ujung Gading, Lembah Melintang District, West Pasaman Regency. This literary research adopts a descriptive qualitative method. Data were collected from the lines, rhymes, and stanzas of pantun featured in a wedding ceremonial speech, as well as interviews with three informants. Data collection techniques included direct observation and interviews, with data validity ensured through triangulation. Data analysis involved classification, interpretation, and presentation of findings. The results show that pantun in ceremonial speeches possess a physical structure characterized by symmetrical typography, aesthetic diction rich in cultural meaning, and the use of regional vocabulary such as horas, martikte, pasu-pasu, roantos, marhite, and jolanta. The rhythm of the pantun tends to follow a free pattern, featuring auditory, visual, and tactile imagery. Its inner structure comprises themes, emotions, tone, and messages that reflect sociocultural values such as respect, affection, and hope for the married couple. In terms of function, pantun serve expressive and directive purposes. The expressive function is dominant, used to convey respect, blessings, and pride, while the directive function subtly communicates moral values and customary messages. These findings indicate that pantun are not merely rhetorical ornaments in traditional speeches but also serve as vital tools for the transmission of Minangkabau cultural values.